2017
DOI: 10.1002/pbc.26599
|View full text |Cite
|
Sign up to set email alerts
|

Impaired immune function in children and adults with Fanconi anemia

Abstract: Background Fanconi anemia (FA) is a rare genetic disorder characterized by genome instability, bone marrow failure, and cancer predisposition. Previously, small studies have reported heterogeneous immune dysfunction in FA. Procedure We performed a detailed immunologic assessment in a large FA cohort who have not undergone bone marrow transplantation or developed malignancies. Comprehensive quantitative and functional immunologic assessment of 29 FA individuals was compared to healthy age-matched controls. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 19 publications
3
35
0
Order By: Relevance
“…Just as important, HPV titers should be monitored for many years post vaccination to evaluate sustainability and to address the question of need for booster vaccine in this cancer prone population, particularly as some parents of children with FA request to have their younger children vaccinated. Additionally, B cell deficiency and dysfunction were observed in almost half of the participants with FA, a finding confirming previous reports [26, 27]. Immune dysfunction seen in participants with FA can change over time and response to vaccine may differ depending on their age at vaccination.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Just as important, HPV titers should be monitored for many years post vaccination to evaluate sustainability and to address the question of need for booster vaccine in this cancer prone population, particularly as some parents of children with FA request to have their younger children vaccinated. Additionally, B cell deficiency and dysfunction were observed in almost half of the participants with FA, a finding confirming previous reports [26, 27]. Immune dysfunction seen in participants with FA can change over time and response to vaccine may differ depending on their age at vaccination.…”
Section: Discussionsupporting
confidence: 88%
“…Nevertheless, molecular and cellular mechanisms responsible for protection from and clearance of HPV infection are not completely understood [23]. Since our group and others have previously shown heterogeneous immune defects in those living with FA, a better understanding of the role of HPV and host immunity would allow for a more thoughtful approach towards prevention of HPV infection and risk reduction for SCC in this vulnerable population particularly as the HPV vaccine is available and recommended [2427]. …”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted that FANC pathway-deficient mice present mild hematopoietic phenotypes (49). The Fanca -/model we used (50) is known to present reduced platelet counts, which mimics patient thrombocytopenia, and altered immunoglobulin formation in association with alterations in the DNA damage response and B cell differentiation (51)(52)(53), abnormalities already reported in FA patients (54). Nevertheless, Fanca -/and WT mice, independently of their ages (3-6 months old, i.e., young, or more than 1 year old, i.e., old) present similar levels of Lin -Sca + Kit + (LSK) cells and their 3 subpopulations, longterm HSCs (LT-HSCs, Flt3 -CD34 -), short-term HSCs (ST-HSCs, Flt3 -CD34 + ), and multipotent progenitors (MPPs, Flt3 + CD34 + ), on which the maintenance of hematopoiesis depends (Figure 4, A-C).…”
Section: Fanc Core Complex Loss Of Function Leads To Mitf Overexpressmentioning
confidence: 93%
“…Fanconi anemia (FA), the most common form of the aplastic anemias, is a recessive genetic disorder with an estimated carriership of 1:300 and disease prevalence of 4—7:1 000 000 . FA is characterized by genome instability, bone marrow failure, and cancer predisposition . Several studies showed a significant humoral and cellular immune dysfunction in patients with FA .…”
Section: Introductionmentioning
confidence: 99%
“…3 Several studies showed a significant humoral and cellular immune dysfunction in patients with FA. 3 As a result of the high variety in presentation, the diagnosis of FA will often be confirmed after the pancytopenia appears. The most frequently associated congenital malformations are those of the skeletal system, mainly radius and thumb.…”
Section: Introductionmentioning
confidence: 99%